Are Environmental Concerns Deterring People from Having Children? - Ben Lockwood; Nattavudh Powdthavee; Andrew J. Oswald (Institute of Labor Economics (IZA), 2022)
Are 'green' environmental concerns – about climate change, biodiversity, pollution – deterring today's citizens from having children? This paper, which we believe to be the first of its kind, reports preliminary evidence consistent with that increasingly discussed hypothesis. Our study has a simple longitudinal design. It follows through time a random sample of thousands of initially childless men and women in the UK. Those individuals who are committed to a green lifestyle are found to be less likely to go on to have offspring. Later analysis adjusts statistically for a large set of potential confounders, including age, education, marital status, mental health, life satisfaction, optimism, and physical health. Because there might be unobservable reasons why those who are pro-environmental may be less likely to want a child, and to try to ensure that the finding cannot be explained by selection and omitted variables, the paper explores Oster's (2019) bounds test. The paper's final estimated effect-size is substantial: a person entirely unconcerned about environmental behaviour is found to be approximately 60% more likely to go on to have a child when compared to a deeply committed environmentalist.
Keywords: J1; Q50; 330; fertility; child-bearing; climate change; environment; green